The Impact of Incretin-Based Medications on Lipid Metabolism - Habib Yaribeygi; Mina Maleki; Alexandra E. Butler; Tannaz Jamialahmadi; Amirhossein Sahebkar (Journal of Diabetes Research)
Pathophysiological pathways that are induced by chronic hyperglycemia negatively impact lipid metabolism. Thus, diabetes is commonly accompanied by varying degrees of dyslipidemia which is itself a major risk factor for further macro- and microvascular diabetes complications such as atherosclerosis and nephropathy. Therefore, normalizing lipid metabolism is an attractive goal for therapy in patients with diabetes. Incretin-based medications are a novel group of antidiabetic agents with potent hypoglycemic effects. While the impact of incretins on glucose metabolism is clear, recent evidence indicates their positive modulatory roles on various aspects of lipid metabolism. Therefore, incretins may offer additional beneficial effects beyond that of glucose normalization. In the current review, how these antidiabetic medications can regulate lipid homeostasis and the possible cellular pathways involved are discussed, incorporating related clinical evidence about incretin effects on lipid homeostasis.